An investigation on a trachea air flow pattern in an intubated patient: Airway edema case - Sanpanich, A.; Masomtob, M.; Phasukkit, P.; Kajornpredanon, Y.; Daochai, S.; Sroykham, W.; Petsarb, K.; Phairoh, C.; Angkhananuwat, W. (My University, 2017)
In a respiratory failure patient, an artificial ventilation is commonly performed by using a mechanical ventilator particularly in an ICU ward. On such a case, an endotracheal tube (ETT) must be inserted into patient's airway and following by a balloon cuff blowing in order to fix and act as a sealed artificial airway for an artificial ventilation. However, those implementations adversely affect to tracheal tissue-epithelial layer and probably damaging a larynx and vocal cord zone. After a ventilator weaning and an extubating process, some patients always suffering with a larynx or tracheal edema symptom or postextubation stridor (PES) in which patient airway is narrowed or swelling due to a long term pressurization by the ETT balloon cuff. This mainly causes a difficulty in a spontaneous breathing. In general, a cuff leak test is a common medical maneuver used in order to predict a larynx or tracheal edema possibility after ETT was removed. Air volume different between an inspired volume (Vtì) and an expired volume (Vie) normally should be higher than 100 mL or 10%. In this paper, we propose an investigation of an airflow pattern on an intubated patient in the cuff leak test process in order to understand and support a prediction of the tracheal edema before perform an ETT extubation. The study was performed in an intubated trachea by using a simulation of an airflow pattern, air volume prediction in a normal intubated case and during cuff leak test process with no edema and edema case. Although, this simulation was intently implemented in a simple intubated trachea model, however the obtain results imply us a practical information and will be used as a basic implementation for a further study, especially in case of variety in the ETT intubation or cuff less ventilation even more complication case in the near future.
Keywords: airway airflow pattern; CFD; cuff leak test; larynx-trachea edema; stirdor sound